Enjoy tubers free from Phytophthora - Misra, R S (Indian Horticulture, 2019)
Leaf blight of taro caused by Phytophthora colocasiae, cassava tuber rot caused by P.palmivora and leaf blight of Amorphophallus are serious diseases of tropical tuber crops. Their timely management is the need of the hour.